2015
DOI: 10.3906/yer-1411-9
|View full text |Cite
|
Sign up to set email alerts
|

Petrography and palynology of Late Oligocene and Middle Miocene coals in the Gelibolu peninsula, NW Turkey

Abstract: However, all of them have focused on the geology of the coal-bearing strata and there is no study regarding the coal petrographic and palynological properties of these coals.The aim of this paper is to determine the maceral and palynological composition of the two different coal-bearing formations, which are the Late Oligocene Osmancık and Middle Miocene Gazhanedere (Figures 1 and 2). We also aim to determine the depositional conditions of the coals using coal petrography, including maceral ratios, by the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The annual average temperature of palynomorphs was investigated to explain the transition during the Rupelian and Chattian, which revealed climatic cooling, vegetation and pollen changes of the pollen assemblages in coastal deposits. Demirtaş et al (2015) studied the late Oligocene palynomorphs from the Middle Miocene coals of the Gelibolu Peninsula. Samples were taken from coal zones in two different regions; coal petrography was used to examine the storage conditions of the two coal zones along with their organic petrography, compositions, maceral ratios and palynological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The annual average temperature of palynomorphs was investigated to explain the transition during the Rupelian and Chattian, which revealed climatic cooling, vegetation and pollen changes of the pollen assemblages in coastal deposits. Demirtaş et al (2015) studied the late Oligocene palynomorphs from the Middle Miocene coals of the Gelibolu Peninsula. Samples were taken from coal zones in two different regions; coal petrography was used to examine the storage conditions of the two coal zones along with their organic petrography, compositions, maceral ratios and palynological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It is widespread throughout the Oligocene of Turkey, but is richer in the Late Oligocene than Early Oligocene, and has only limited distribution in Miocene deposits (e.g. Akgün et al, 2013; Akgün & Sözbilir, 2001; Akkiraz & Akgün, 2005; Akyol, 1971; Batı, 1996; Demirtaş, Bozcu, Koşun, & Akkiraz, 2015; Ediger et al, 1990; Kayseri‐Özer et al, 2017; Nakoman, 1966; Sancay et al, 2006; Şengüler & Akkiraz, 2014). This view fits well with the data of Ediger et al (1990) who emphasized that this species culminates in the Upper Oligocene strata of the Thrace Basin, north‐west Turkey, while its quantities declined throughout the Early Miocene, and even survived in the Pliocene (Ediger et al, 1990).…”
Section: Biostratigraphymentioning
confidence: 99%
“…Even the Oligocene (late Rupelian) coal exposures of the Gök-çeada Basin, located on the western side of the Biga Peninsula, (Figure 1) may be correlated with the Thrace Basin since the palynomorph assemblages are more or less comparable. Both basins included high percentages of rotan palm Calamus (morpho-species Dicolpopollis kockelii) peaking during the Chattian (Late Oligocene) as indicated by Batı (1996), Ediger et al (1990), Akgün et al (2013) and Demirtaş et al (2015).…”
Section: Introductionmentioning
confidence: 95%
“…In particular the Thrace Basin is well known since it mostly includes the Oligocene lignite-bearing deposits (e.g. Akgün et al, 2013;Akyol, 1971;Batı, 1996;Bozcu et al, 2015;Demirtaş, Bozcu, Koşun, & Akkiraz, 2015;Ediger, Bati, & Alişan, 1990;Görür & Okay, 1996;İslamoğlu et al, 2010;Less, Özcan, & Okay, 2011;Özcan et al, 2010;Sakınç, Yaltırak, & Oktay, 1999;Siyako & Huvaz, 2007, Figure 1). Geological studies indicated that the spread of Oligocene coaly sequences was thought to be only in the Thrace Basin.…”
Section: Introductionmentioning
confidence: 97%